2003
DOI: 10.1089/108497803770418364
|View full text |Cite
|
Sign up to set email alerts
|

Improved Radiolabeling of PEGylated Protein: PEGylated Annexin V for Noninvasive Imaging of Tumor Apoptosis

Abstract: We have developed a one-step procedure to introduce both polyethylene glycol (PEG) and the metal chelator diethylenetriaminepentaacetic acid (DTPA) to proteins through a heterofunctional PEG precursor. The PEG precursor contains DTPA at one end and an amine-reactive isothiocyanate (SCN-) functional group at the other end. It was obtained as lyophilized powder and could be stored at 4 degrees C for several months. Protein conjugation was achieved by simply mixing the proteins and the PEG precursor SCN-PEG-DTPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…The motivation for the present study was to demonstrate that the short blood circulation time of AnxA5 as a typical small protein-based imaging probe can be extended by recombinant expression with XTEN as an alternative to PEGylation (22). We successfully adapted the method of Schellenberger et al (7) to design an XTEN-AnxA5 fusion protein with a cysteine coupling site and demonstrated its biologic activity by flow cytometry and fluorescence microscopy in vitro and its extended blood half-life of 1 h, compared with unmodified AnxA5, by nuclear imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation for the present study was to demonstrate that the short blood circulation time of AnxA5 as a typical small protein-based imaging probe can be extended by recombinant expression with XTEN as an alternative to PEGylation (22). We successfully adapted the method of Schellenberger et al (7) to design an XTEN-AnxA5 fusion protein with a cysteine coupling site and demonstrated its biologic activity by flow cytometry and fluorescence microscopy in vitro and its extended blood half-life of 1 h, compared with unmodified AnxA5, by nuclear imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Second, PEGylation can result in partial inactivation of the target protein, especially when using amine-directed coupling (22), a complication to which AnxA5 is especially susceptible (23). Third, PEGylation often results in mixtures of proteins with zero-, one-, and multiple-coupled PEGs, which are hard to separate (22), in addition to the fact that PEG is usually provided as a mixture of heterogeneous lengths (24). In contrast, XTEN-coupled products are developed by genetic fusion to a defined amino acid sequence that ensures a monodisperse final compound (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating half-lives of ANV-KPIs are likely similar to that of ANV, which was reported to have a rather short half-life of 4.2 minutes in mice. 53 It is of great interest that the test molecules were administered at very low doses (10 to 100 g/kg) by bolus injection 5 minutes before induction of vessel damage, yet the occlusion times were prolonged from 57 minutes for the control to up to about 2 hours for the treated animals. This suggested that ANV and ANV-KPIs might exert a passivating effect on the thrombogenic sites and maintain vascular patency after their clearance from the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent method for radiolabeling PEG requires modification of the terminal hydroxyl group. Depending on the modification of the PEG, a range of radiolabels can be incorporated onto the PEG molecule; these include 125 I, 14 C, 18 F, and 111 In (Yamaoka et al, 1994;Wen et al, 2003;Chen et al, 2004;Shemilt et al, 2004). These methods are generally not applicable to PEGylated proteins because radiolabeling is performed at the terminal hydroxy groups of the molecules, and these groups are frequently either methylated or used to link to the protein or linker.…”
Section: Feasibility Of Metabolism Studies With Pegylated Materialsmentioning
confidence: 99%